PROGRAM MEDIA RADIO, TELEVESI, DAN MEDIA ONLINE: RADIO, TELEVESI, AND ONLINE MEDIA PROGRAMS - Winda Kustiawan; Amran Sahputra Tanjung; Azbar Rifai; Melda Wati Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2022)
The programs and strategies that must be carried out by the broadcast media in dealing with this are the coordination of the national revival movement which is directed primarily at strengthening the resilience of the community and the nation against all efforts to destroy the character and cultural values of the nation. , the state, not only very broad, but also fast and efficient. simultaneously. Broadcast media in carrying out their duties as service media, disseminator of information, inheritance of cultural values, educating, entertaining, social control, advertising media, must be able to convey messages so that the public can obtain clear, complete, honest, ethical and moral and objective information. The conclusion of this discussion is that the function of media coverage and broadcasting needs to be studied to make it easier if you want to do a media program, and some of the functions of the media themselves in providing knowledge to the audience in accordance with ethics. . value for broadcasting and reporting activities.